Yiqi Fumai lyophilized injection ameliorates pulmonary arterial hypertension induced right heart dysfunction through ACE2-Ang (1-7)-Mas axis and PI3K/Akt/eNOS pathway - Xiao-ying Han; Yi Zhang; Xin-yu Zhang; Hai-xia Ji; Wen-zhe Wang; Ou Qiao; Xia Li; Juan Wang; De-kun Li; Ai-chun Ju; Chang-xiao Liu; Wen-yuan Gao (Elsevier, 2022)
Background: Pulmonary arterial hypertension (PAH) is a progressive and presently an incurable disorder disease, which complicates a considerable number of cardiovascular along with respiratory conditions. The treatment options available to prevent advancement of PAH to right ventricular (RV) dysfunction hypertrophy, as well as failure are few. Although it has been reported that Yiqi Fumai lyophilized injection (YQFM) plays an indispensable role in protecting the heart, the effect of YQFM on the heart injury caused by PAH is still unclear. Purpose: In this study, we explored whether YQFM can change the results related to PAH-induced heart damage and its mechanism of action. Study design: MCT-induced pulmonary arterial hypertension rat model was established, and YQFM was administered. Methods: The chemical components of YQFM were analyzed by HPLC-QQQ-MS. In vivo experiments were conducted to evaluate the effect of YQFM on right heart dysfunction caused by pulmonary hypertension. All hemodynamic and histology of heart and lung were done at the end of the study. Biochemical measurements and Western blotting prove the expression of related factors and proteins. Results: Compared with the control group, daily administration of YQFM significantly improved the survival rate of rats with severe MCT triggered pulmonary hypertension. Hemodynamic evaluation illustrated that YQFM remarkably lowered mean pulmonary artery pressure and RV systolic pressure. YQFM treatment could reduce right ventricular hypertrophy and fibrosis. Conclusion: YQFM can reduce mortality, RV systolic pressure along with RV injury in PAH induced by MCT. In MCT-induced animal models, YQFM has the therapeutic potential to prevent and reduce the development of PAH. YQFM protects right ventricular hypertrophy in PAH induced by MCT through ACE2-Ang (1-7)-Mas axis and PI3K/Akt/eNOS pathway. Therefore, YQFM may be a useful treatment strategy for the treatment of human PAH and subsequent right heart hypertrophy.